Testing Nano‐Powder and Fused‐Glass Mineral Reference Materials for In Situ Rb‐Sr Dating of Glauconite, Phlogopite, Biotite and Feldspar via LA‐ICP‐MS/MS. Issue 1 (27th December 2022) - Redaa, Ahmad; Farkaš, Juraj; Gilbert, Sarah; Collins, Alan S.; Löhr, Stefan; Vasegh, Davood; Forster, Marnie; Blades, Morgan; Zack, Thomas; Giuliani, Andrea; Maas, Roland; Baldermann, Andre; et al.
Abstract : Reference materials (RMs) with well‐characterised composition are necessary for reliable quantification and quality control of isotopic analyses of geological samples. For in situ Rb‐Sr analysis of silicate minerals via laser ablation inductively coupled plasma tandem mass spectrometry (LA‐ICP‐MS/MS) with a collision/reaction cell, there is a general lack of mineral‐specific and matrix‐matched RMs, which limits wider application of this new laser‐based dating technique to certain minerals. In this work, pressed nano‐powder pellets (NP) of four RMs, GL‐O (glauconite), Mica‐Mg (phlogopite), Mica‐Fe (biotite) and FK‐N (K‐feldspar), were analysed and tested for in situ Rb‐Sr dating, complemented by isotope dilution (ID) MC‐ICP‐MS Rb‐Sr analyses of GL‐O and Mica‐Mg. In addition, we attempted to develop alternative flux‐free and fused 'mineral glasses' from the above RMs for in situ Rb‐Sr dating applications. Overall, the results of this study showed that among the above RMs only two NP (Mica‐Mg‐NP and GL‐O‐NP) were suitable and robust for in situ dating applications. These two nano‐powder reference materials, Mica‐Mg‐NP and GL‐O‐NP, were thus used as primary RMs to normalise and determine Rb‐Sr ages for three natural minerals: MDC phlogopite and GL‐O glauconite grains, and also Mica‐Fe‐NP (biotite). Our in situ analyses of the above RMs yielded Rb‐Sr ages that are in good agreement (within 8%) of published ages, which suggests that both Mica‐Mg‐NP and GL‐O‐NP are suitable RMs for in situ Rb‐Sr dating of phlogopite, glauconite and biotite. However, using secondary RMs is recommended to monitor the quality of the obtained ages. Key Points: Suitable matrix‐matched reference materials for in situ Rb‐Sr dating by LA‐ICP‐MS/MS are needed to apply the technique to wider applications. Mica‐Mg‐NP and GL‐O‐NP are suitable reference materials to date phlogopite and glauconite samples. Use of secondary reference materials is recommended to monitor the quality of the produced ages.